CRP in Patients with Acute Ischemic Stroke in Bangladesh - Amin, Md Robed; Mohammad, Hanif; Ahmed, Kazi Gias Uddin; Sarkar, Devendra Nath (Journal of Medicine, 2014)
Objectives: This aim of the study was to evaluate CRP and the risk factors in ischaemic stroke. Methods: This case control study was carried out from January 2006 to December 2007 in the department of Neurology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka in all the OPD and admitted stroke patients meeting the inclusion and exclusion criteria. Results: Out of 30 patients with ischaemic stroke 28(93.3%) patients had positive C-reactive protein value. 37% stroke patients were smoker. Mean total cholesterol, triglyceride and LDL level were higher and mean HDL level was lower among stroke patients in comparison to controls. 17% of stroke patients were suffering from diabetes mellitus & 80% of stroke patients were hypertensive. Conclusion: C-reactive protein is elevated in the acute phase of ischa emic stroke and could present a prognostic marker. DOI: http://dx.doi.org/10.3329/jom.v15i1.19859 J Medicine 2014; 15: 41-47